2017
DOI: 10.3390/s17112610
|View full text |Cite
|
Sign up to set email alerts
|

HDOMO: Smart Sensor Integration for an Active and Independent Longevity of the Elderly

Abstract: The aim of this paper is to present the main results of HDOMO, an Ambient Assisted Living (AAL) project that involved 16 Small and Medium Enterprises (SMEs) and 2 research institutes. The objective of the project was to create an autonomous and automated domestic environment, primarily for elderly people and people with physical and motor disabilities. A known and familiar environment should help users in their daily activities and it should act as a virtual caregiver by calling, if necessary, relief efforts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…They developed a series of alarms that detected unusual behaviours such as falls, sleep apnoea, incorrect feeding, etc. [35]. Other approaches, such as the one presented in [36], define systems that learn from room-to-room transitions and permanence to detect behaviour changes that may be related with health problems, which are communicated via alarms.…”
Section: Related Work Reviewmentioning
confidence: 99%
“…They developed a series of alarms that detected unusual behaviours such as falls, sleep apnoea, incorrect feeding, etc. [35]. Other approaches, such as the one presented in [36], define systems that learn from room-to-room transitions and permanence to detect behaviour changes that may be related with health problems, which are communicated via alarms.…”
Section: Related Work Reviewmentioning
confidence: 99%
“…The Doppler Radar realized in [3] allows to determine the complex S21 parameter between the transmitting and the receiving antenna. The received signal is modulated both in amplitude and phase by chest movement.…”
Section: Formulation Of the Problemmentioning
confidence: 99%
“…The possibility of continuous, non-invasive and simple monitoring would lead to a reduction in hospital costs and a greater self awareness of the patient's health status. The use of electromagnetic (EM)sensors for remote respiration monitoring has proved to be very effective [2][3]. This type of sensor is very promising for domestic use as it respects the subject's privacy, it has an excellent ability to penetrate the fabrics and therefore it can be used even when the subjects are dressed.…”
Section: Introductionmentioning
confidence: 99%
“…Since over the years a proper maintenance plan resulted in management, performance, and profit benefits (Lucantoni et al, 2019), the idea of maintenance has moved to a more scientific policy, namely Preventive maintenance, for failure occurrences prevention and proper operating condition restoration in manufacturing (Ding & Kamaruddin, 2015). Among strategies, Predictive Maintenance (PdM) is considered one of the most interesting in the field of fault prediction, continuously growing with the technological advancement in manufacturing: due to the growing number of machines, systems, equipment, and products, DM models for data management through algorithms analytics (Frontoni et al, 2017) has demonstrated interesting prediction capabilities and decision making from a PdM perspective (Paolanti et al, 2017). In this context, the current paper aims to develop an algorithm for failure prediction.…”
Section: Introductionmentioning
confidence: 99%